Fighting the Lack of Wildlife Friendly Architecture: Implementation of Automatic Bird Fountains on Facultad Regional Parana´s Rooftops - Garavello, Matias; Noya, Luciano; Rios, Araceli (My University, 2023)
Summary— Paraná, which is the capital city of Entre Ríos, is next to the Paraná River, which is one of the most important rivers in South America. The Paraná River’s great flow and long extension make it the perfect water source for hundreds of species of animals. However, the construction of a big city next to it disrupted the ecosystem of these animals. The main objective of this project is to address the lack of access to water for indigenous bird species within the urban environment. To achieve this aim, we will describe a possible solution that consists of the implementation of automatic bird fountains on the rooftops of Universidad Tecnológica Nacional (UTN) Facultad Regional Parana (FRP). In this work, the information is organized as follows. First, the problem, which is located in the city of Parana, is briefly addressed. Secondly, there is a description of the context where the problem is located, with a special focus on the area of interest for this project, which is the southwest area of the city. Then, the problem to be addressed, which affects thousands of birds in the city, is described. After this, there is a description of figures that show the problem and the areas surrounding UTN FRP premises where the problem is found. Next, the causes and consequences of this problem are analysed. Finally, the proposal of the solution is explained along with its strengths and weaknesses. It is expected that this work can raise awareness about the importance of reducing bird abandonment in the city as well as decreasing bird extinction in this area. By means of this work, we hope to inspire many citizens to take care of birds by applying similar sustainable measures in other areas of the city.

Resumen— Paraná, que es la capital de Entre Ríos, está al lado del río Paraná, que es uno de los ríos más importantes de América del Sur. El gran caudal y gran extensión del río Paraná lo convierten en la fuente de agua perfecta para cientos de especies de animales. Sin embargo, la construcción de una gran ciudad al lado alteró el ecosistema de estos animales. El principal objetivo de este proyecto es abordar la falta de acceso al agua para las especies de aves autóctonas en el entorno urbano. Para lograr este objetivo, describiremos una posible solución que consiste en la implementación de bebederos automáticos para pájaros en las azoteas de la Facultad Regional Paraná (FRP) de la Universidad Tecnológica Nacional (UTN). En este trabajo la información se organiza de la siguiente manera. Primero se aborda brevemente el problema, que se ubica en la ciudad de Paraná. En segundo lugar, se describe el contexto donde se ubica el problema, con especial enfoque en la zona de interés de este proyecto, que es la zona suroeste de la ciudad. Luego, se describe el problema a abordar, que afecta a miles de aves en la ciudad. A continuación, se describen unas figuras que muestran el problema y las zonas aledañas a las instalaciones de la UTN FRP donde se encuentra el problema. A continuación, se analizan las causas y consecuencias de este problema. Finalmente se explica la propuesta de solución junto con sus fortalezas y debilidades. Se espera que este trabajo pueda generar conciencia sobre la importancia de reducir el abandono de aves en la ciudad, así como disminuir la extinción de aves en esta zona. A través de este trabajo esperamos inspirar a muchos ciudadanos a cuidar de las aves aplicando medidas sostenibles similares en otras zonas de la ciudad.
Keywords: Inglés I, automatic bird fountain, lack of water for animals, solar energy, sustainable bird care.; Inglés I, fuente automática para aves, falta de agua para animales, energía solar, cuidado sostenible de aves.